Social Situation Analysis During The Pandemic Outbreak In The Novel The Stand By Stephen King - Ali, Muhammad Ilham; Herminus Efrando Pabur; Ceisy Nita Wuntu (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2023)
This research aims to analyze the social situation during the flu-influenza pandemic in the novel "The Stand" by Stephen King. Researchers completed the data for this study using descriptive qualitative analysis techniques. The data collection in this article is the novel "The Stand" and secondary data are internet resources and journals and the technique of collecting data using note-taking. The technique analysis data used an objective approach to examine how literary works relate to the current (real-time) context. The method of analysis involves looking for patterns of behavior, changes in social norms, and individual responses to uncertainty and health threats. The results revealed that the pandemic outbreak catalyzed significant social change in the novel, giving rise to new power dynamics, competition, and collaboration among survivor groups. The results of this study illustrate the Influenza flu pandemic that almost claimed the entire population in the world and how those who are still alive survived until this pandemic problem is over, face loneliness, despair, belief (religion), and responsibility. This article also provides deep insights into how authors use fiction to reflect and depict social situations during health crises. The implications of these findings may provide further understanding of the complexity of human interactions during difficult times and create awareness of the importance of solidarity and adaptation in the face of global challenges.